Ações antioxidantes e imunológicas do selênio em cães - Putarov, Thaila Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aims of this study were to evaluate the effects of selenium sources and levels on the immune response of adult dogs. Treatments were: CO - control diet with sodium selenite addition, totalizing 0.13 ppm of Se; SO33 - control diet + Se-yeast, totalizing 0.33 ppm of Se; SO66 - control diet + Se-yeast, totalizing 0.66 ppm of Se; and SO99 - control diet + Se-yeast, totalizing 0.99 ppm of Se; SI66 - control diet + sodium selenite, totalizing 0.66 ppm of Se. Animals underwent though an adaptation period of 90 days and received the CO diet; the experimental phase lasted 120 days when animals received the tested diets and samples were taken. Blood samples were collected on days 0, 30, 60, 90 e 120 of experimental phase to identify the leukocyte population (IF), to determine the phagocyte activity (FA) of neutrophils and monocytes, the proliferation of peripheral blood mononuclear cells (PIMC), the production of reactive oxygen (ROS) and nitrogen (NOS) intermediate species. Serum samples were also taken at 5, 10, 15 and 20 days after SRBC solution inoculation to determine the levels of IgG and IgM anti-SBRC. Fresh stool were obtained to evaluate the fecal IgA on days 0 and 120. Delayed-type hypersensitivity skin test (DTH) was conducted with the animals on day 120. The PICM reduced within time for all treatments, but on day 120th SO33-fed animals had the higher proliferation than the other treatments (P<0.05). The FA of neutrophils and monocytes was lower at 120th (P<0.0001) and a trend was observed for higher AF of neutrophils from SO33-fed dogs (P=0.0863). The population of CD5+ lymphocytes increased after 60 days and there was a trend for higher CD5+CD8+ lymphocytes count for animals fed CO, SO99 and SI66. The CD4+/CD5+ ratio was higher for animals fed SO33 and SO66 (P<0.0001). The values of IgG, IgM, IgA, ROS and NOS, and the DTH response were not influenced by treatments. Dose of ...

Os objetivos do trabalho foram avaliar o efeito de níveis e fontes de selênio na resposta imune de cães adultos, para isto cinco dietas foram avaliadas. Os tratamentos foram: CO - dieta basal com adição de selenito de sódio, totalizando 0,13 ppm de Se; SO33 - dieta basal + Se-levedura totalizando 0,33 ppm de Se; SO66 - dieta basal + Se-levedura totalizando 0,66 ppm de Se; SO99 - dieta basal + Se-levedura totalizando 0,99 ppm de Se; SI66 - dieta basal + selenito de sódio totalizando 0,66 ppm de Se. Os animais foram submetidos a um período de adaptação de 90 dias com a ração CO seguidos de 120 dias de fase experimental e recebendo as dietas testes, totalizando 210 dias. Amostras de sangue foram colhidas nos dias 0, 30, 60, 90 e 120 da fase experimental para: imunofenotipagem de leucócitos (IF), atividade fagocítica (AF) de monócitos e neutrófilos, índice de proliferação de células mononucleares do sangue periférico (IPCM), produção de intermediários reativos do oxigênio (H2O2) e do nitrogênio (NO-3). Para a determinação de anticorpos IgG e IgM específicos contra eritrócito de carneiro (SRBC) foram coletadas amostras de sangue 5, 10, 15 e 20 dias após inoculações de soluções de SRBC que ocorreram nos dias 60 e 90 da fase experimental. Fezes frescas foram colhidas para determinação da IgA fecal nos dias 0 e 120, e foi realizado o teste de hipersensibilidade cutânea tardia (DTH) aos 120 dias. O IPCM diminuiu em todos os tratamentos ao longo do experimento, porém aos 120 dias os animais do tratamento SO33 apresentaram a maior IPCM comparado aos demais (P<0,05). A AF de neutrófilos e monócitos foi menor aos 120 dias (P<0,0001) e houve tendência de maior AF por neutrófilos nos cães suplementados com 0,33 ppm de Se orgânico (P=0,0863). O número de linfócitos CD5+ aumentou após 60 dias de experimento para todos os tratamentos. Houve uma tendência para maior ...
Keywords: Glutationa; Linfocitos; Minerais na nutrição animal; Glutathione